Recurrent Pregnancy Losses and Gestational Age Are Closely Related: An Observational Cohort Study on 759 Pregnancy Losses. (May 2015) - Coccia, Maria Elisabetta; Rizzello, Francesca; Capezzuoli, Tommaso; Spitaleri, Marina; Riviello, Chiara
To assess the accurate dating of the cessation of pregnancy in patients with recurrent pregnancy loss (RPL) and to evaluate the incidence and recurrence rate of pregnancy losses in similar gestational age. In a retrospective cohort study, couples with history of RPL and availability of precise documentation regarding previous pregnancy losses were included. The vast majority of losses occurred within the first trimester. In patients experiencing more than 2 miscarriages in the same gestational stage, a tendency for recurrent losses around the same period of gestation was observed. Overall, the probability of losses at different gestational stages goes down with increasing number of miscarriages at the same stage. The study supports the need to ascertain data regarding the timing of pregnancy loss as accurately as possible for prognosis of future pregnancies and management of couples. A classification for unexplained RPL based on gestational age of miscarriages could help researchers to better investigate RPL.